2018
DOI: 10.1093/scan/nsy114
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing monitoring of mindwandering in avoidant grief through cortico-basal-ganglia interactions

Abstract: An avoidant grief style is marked by repeated and often unsuccessful attempts to prevent thinking about loss. Prior work shows avoidant grief involves monitoring the external environment in order to avoid reminders of the loss. Here we sought to determine whether avoidant grievers also monitor the internal environment in attempts to minimize conscious awareness of loss-related thoughts. Individuals bereaved of a first-degree relative, spouse or partner within the last 14 months participated in a functional mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This contradictory response may be mediated via interactions between a broader cortical network comprising the default mode, cognitive control, and salience regions and the OFC-basal ganglia subnetwork. 44 Moreover, differential activity in the middle temporal gyrus and the cuneus, additional brain areas seen in our whole cerebrum analyses (Figure S6) have been previously reported in studies of acute grief from romantic rejection 26 and after death of an unborn child. 20 In LLD, frontal lobe hypoactivation and diminished amygdala Fc with the executive control and salience regions are reported, relative to HC individuals.…”
Section: Discussionsupporting
confidence: 73%
“…This contradictory response may be mediated via interactions between a broader cortical network comprising the default mode, cognitive control, and salience regions and the OFC-basal ganglia subnetwork. 44 Moreover, differential activity in the middle temporal gyrus and the cuneus, additional brain areas seen in our whole cerebrum analyses (Figure S6) have been previously reported in studies of acute grief from romantic rejection 26 and after death of an unborn child. 20 In LLD, frontal lobe hypoactivation and diminished amygdala Fc with the executive control and salience regions are reported, relative to HC individuals.…”
Section: Discussionsupporting
confidence: 73%
“…Schneck et al suggested that these two networks are responsible for the avoid-approach conflict characteristic of avoidant grief, with the d-SA network monitoring for cues related to the deceased in order to prevent the d-MR network activating. Paradoxically, the study found that in the absence of a cue, participants with avoidant grief, as indicated by the IES, had more frequent intrusive thoughts about the deceased than those with normative grief, suggesting that heightened d-SA primes the brain for deceased-related thoughts (Schneck et al 2019b).…”
Section: The Basal Gangliamentioning
confidence: 96%
“…A second study by the same group (Schneck et al 2019b) identified two separate patterns characteristic of avoidant grievers, as indicated by the IES: a frontotemporoparietal network for deceased-related selective attention (d-SA) and the aforementioned basal gangliaorbitofrontal network for mental representation of the deceased (d-MR). Schneck et al suggested that these two networks are responsible for the avoid-approach conflict characteristic of avoidant grief, with the d-SA network monitoring for cues related to the deceased in order to prevent the d-MR network activating.…”
Section: The Basal Gangliamentioning
confidence: 98%
See 1 more Smart Citation
“…However, as a follow up to the last study, a multivoxel pattern analysis was used to identify a pattern of brain activity associated with intrusive deceased-related thoughts. The authors focused on interacting connectivity between the salience network, and the ventral attention and default networks (72). This interaction was different among those high and low in deliberate avoidance as a coping strategy.…”
Section: Adaptation Of the Brain During Griefmentioning
confidence: 99%